Research Progress and Outlook on Critical Characteristics of Submerged Floating Tunnels. (2016) - Hao, Ding; Qinxi, Li; Shuping, Jiang; Ke, Li
Abstract: As a new traffic structural form, submerged floating tunnels are still in the initial engineering stage. To focus on the research direction as soon as possible, it is necessary to conclude and make contrastive analysis on the research results of submerged floating tunnels. The section forms, the actions of wave force and ocean current force, structural dynamic response and anchor cable stability etc of submerged floating tunnels are selected to serve as the critical indexes of characteristics or roles, being the main analysis object. Based on a great deal of research and investigation on scientific and technical literatures, the research methods, conclusions and consensuses etc are compared, and the research blank and development trend are analyzed. The results indicate: (1) the section forms are determined based on the circumstance of flowing water. An experimental study under large Reynolds number needs to be carried out in the future; (2) According to the actual environmental research, wave force can serve as one of the important bases for the determination of suspension depth; (3) The law of ocean current effect of submerged floating tunnels requires further empirical coefficient research, and fatigue damage also can serve as future research direction; (4) Dynamic response can concentrate on large-scale model experiment as well as the influence of traffic behavior in submerged floating tunnels under dynamic response; (5) Anchor cable stability can focus on vibration reduction method of anchor cable character parameters and semi-active or active vibration reduction control method of anchor cable itself; (6) The future research emphasis should be laid on the large-scale submerged floating tunnel model experiment in complex water area environment. The above conclusions point out the direction for the future research in the field.